Strategi Politik Muhammad Ikhsan Darwis dalam Pemenangan Pemilihan Legislatif Tahun 2024 di DAPIL I Kota Kupang (Lembaga Pengembangan Kinerja Dosen, 2025)
The focus of this paper is to examine the political strategy of Muhammad Ikhsan Darwis in winning the 2024 Legislative Election in Electoral District I of Kupang City, using the 4P political marketing theory by Niffenger: Product, Promotion, Price, and Place. In terms of Product, Ikhsan’s public image is shaped by his clean, caring, and inclusive personal character, as well as his active involvement in various socio-religious organizations such as HIPMI, NU, KKSS, and PPIA, which reinforce his appeal among young voters. His Promotion strategy was realized through campaign tools (APK) that were presented in a simple yet strategic manner, reflecting a courteous and down-to-earth personality. For Price, he implemented both economic and psychological pricing strategies by managing campaign funds efficiently and strengthening his reputation through his educational background and organizational experience. Lastly, in the Place dimension, Ikhsan adopted an inclusive and spiritual approach, leveraging strong grassroots support from communities like KKSS and the Bugis ethnic group. These four strategies were successfully executed, leading to Muhammad Ikhsan Darwis’s election as a legislative candidate representing the Golkar Party in Electoral District I of Kupang City.